Criteria for collection development and management in museums. Systematized Review - Flores-Fernández, Cherie; Inostroza González, Carolina; Santander Campos, Matías; Vilches Sandoval, Egon (Revista General de Información y Documentación, 2022)
The purpose of this research was identify the criteria of collection management and development in museums, through a systematized review. For the development of the bibliographic search was contemplated the use of ten information resources: Dialnet, Jstor, La Referencia, Proquest, Repositorios Latinoamericanos, REDIB, Scopus, Taylor & Francis, Wiley and Wos. 32 documents were selected for analysis and then they were split in five groups according to the type of collections contained in the museums: general collections, human nature collectiones (artifacts and anthropological), art collections, nature collectiones (biology, zoology, entomology,among others) and archaeological collections. It is concluded that currently the museums search for modernize their rol as cultural entities, and the implementation and use of new technologies for the benefit of them and the community; besides it persists in the use and distribution of the museum´s space as a fundamental pillar for the preservation and exhibition of the collections and it glimpses that determined collection management criteria are exclusive or get great importance for the institutions according to the nature and composition of such collections.